Minimizing Net Energy Consumption in Vinyl Chloride Monomer (VCM) Production using Heat-Integrated Process Design - Faith Nadine Rachmantoro; Alya Marsya Talitha; Andanafifajri Ahda Maulana; Chyntami Fredella Sitorus (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Vinyl chloride monomer (VCM) is a key intermediate in polyvinyl chloride (PVC) production, and its manufacture via thermal cracking of 1,2-dichloroethane (EDC) is highly energy intensive. This study aims to reduce the net energy demand of the EDC–VCM section through a heat-integrated process design. A steady-state simulation of the conventional EDC cracking and distillation train was developed as an industrial benchmark. Based on this model, a modified configuration was introduced by adding a feed–effluent heat exchanger to recover heat from the hot reactor effluent and preheat the combined fresh and recycled EDC feed, while maintaining reactor operating conditions and product specifications. Energy performance was evaluated by comparing heating and cooling duties of major equipment. The heat-integrated design lowered the total utility requirement from 9.39 × 10⁷ to 7.93 × 10⁷ kJ/h, equivalent to a 15.5% reduction in external energy demand and reducing total energy cost by 4.3%. These results demonstrate that a simple heat-exchanger retrofit can significantly improve energy efficiency in VCM production, providing a practical route to reduce utility consumption and operational costs. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).